Examining SERVQUAL instrument on the study of relationship between customer satisfaction and the service quality of UiTM Jengka Pahang panel clinics / Nurul Nadia Abd Aziz … [et al.] - Abd Aziz, Nurul Nadia; Tarmuji, Nor Habibah; Samsudin, Mawarti Ashik; Baharum, Norzie Diana (2011)
The purpose of this paper is to examine the suitability of SERVQUAL instrument as a measurement of UiTM employees' satisfaction and panel clinics service quality. The main instrument of this study is a set of questionnaire adapted from Etgar & Fuchs (2009). Some modifications were made to the items in questionnaire in order to suit the context of physician. This study found that all the variables of SERVQUAL instrument except "Assurance" variables are significant at five percent significance level. Since this study was only limited to employees at UiTM Jengka, any suggestion in this study would be considered premature and could only be used as a reference. The findings cannot be generalized to the broader population of UiTM. The study also does not look into variables other than SERVQUAL dimensions that may have influenced customer satisfaction. The results of this study will significantly contribute to the new knowledge on service quality of panel clinics. The data gathered will also benefit the staff of Universiti Teknologi MARA in choosing a good panel clinic with quality service. Until now, there is no study conducted to investigate the service quality of panel clinics in Jengka, Pahang. It is hoped that the present study will lead to the improvement of the panel clinics wherever necessary.